2019
DOI: 10.1139/cgj-2017-0730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of installation effects on set-up of field displacement piles in sand

Abstract: The paper presents results from a new series of tests on displacement piles in sand, involving different installation modes, and combines these with results from previous tests at the same site as well as with test data at two other well-investigated sand sites to provide fresh insights into factors affecting “short-term” capacity and set-up of shaft friction. It is shown that the shaft capacity measured shortly after installation reduces systematically with the logarithm of the number of impact blows or jacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Tavenas & Audy (1972) found that the axial capacity of driven pre-cast concrete piles increased by approximately 70% over a 20 day period after driving. Similar trends were reported by Fellenius et al (1989), York et al (1994), Long et al (1999), Axelsson (2000aAxelsson ( , 2000b, Jardine et al (2006), Anusic et al (2018) and others, see Fig. 1.…”
Section: Introductionsupporting
confidence: 87%
“…Tavenas & Audy (1972) found that the axial capacity of driven pre-cast concrete piles increased by approximately 70% over a 20 day period after driving. Similar trends were reported by Fellenius et al (1989), York et al (1994), Long et al (1999), Axelsson (2000aAxelsson ( , 2000b, Jardine et al (2006), Anusic et al (2018) and others, see Fig. 1.…”
Section: Introductionsupporting
confidence: 87%
“…This is now a well-known and yet still not fully explored phenomenon, which can be briefly defined as the time-dependency of pile bearing behavior. The causes and consequences of this complex and peculiar aspect of foundation engineering are treated extensively in contributions such as Jardine et al (2006), Lim and Lehane (2015), Anusic et al (2019), andCarrol et al (2020) among others. In this work, the restrike test results indicate an average increase in capacity of 6.8% after 7.0 to 7.9 days (RS1 against RS2) and of 20.0% after 25.8 to 27.5 days (RS1 against RS3).…”
Section: Single Pile and Dynamic Pile Load Testsmentioning
confidence: 99%
“…The data in Table 3 of Anusic et al (2019) correspond to different pile installation procedures in different types of sands and field conditions. For one sand type and installation method at one site, there are not enough data to evaluate pile capacity as a function of time; and for example, examine the behavior of C D with elapsed time after pile installation.…”
Section: R a F Tmentioning
confidence: 99%
“…D2 with constant values of C D in the range of 1 to 9 has been superimposed on the pile capacity data in Fig. 1 of Anusic et al (2019). Although in one location in Jebba, Eq.…”
Section: R a F Tmentioning
confidence: 99%